Estimation the Missing Data of Meteorological Variables In Different Iraqi Cities By using ARIMA Model - Nassir, Sura T.; Khamees, Ahmed B.; Mousa, Wassan T. (Iraqi Journal of Science, 2018)
In this paper, ARIMA model was used for Estimating the missing data(air temperature, relative humidity, wind speed) for mean monthly variables in different time series at three stations (Sinjar, Baghdad , AL.Hai) which represented different parts of Iraq from north to south respectively